TRADITION OF KIAI KINSHIP AT ISLAMIC BOARDING SCHOOL IN MADURA (Study on Trah, Kiai Kinship, Islamic boarding school in Sumenep) - Mas'odi, Mas'odi (Program Studi Pendidikan Agama Islam, 2019)
The purpose of this research is to know deeply about social network of kinship tradition or Trah in Madurese tradition which is defined as